Entomopathogenic fungi from Argentina for the control of Schistocerca cancellata (Orthoptera: Acrididae) nymphs: fungal pathogenicity and enzyme activity - Pelizza, Sebastian Alberto (2012)
The South American locust Schistocerca cancellata (Serville) was the most seriousagricultural pest in Argentina during the first half of the last century and remainsas a threat when preventive control measures are relaxed in the outbreak area.In this study, we analysed in the laboratory, the effectiveness of 26 fungal strains(isolated from both insects and soil collected in Argentina) for S. cancellata controland determined the relationship between the chitinase, protease and lipase levels inthese fungi and their insecticidal activities. We observed that Beauveria bassiana(isolate LPSC 1067) caused the highest mortality (9091.03%), the highest valuesof chitinolytic, proteolytic and lipolytic activity were 6.1390.05, 2.5690.11 and2.3390.47, respectively, and the lowest median lethal time was 5.96 days. This isthe first time that a wide variability in chitinase, protease and lipase activity aswell as in virulence has been reported in a representative sample of differententomopathogenic fungal strains from Argentina.